Evoluation of service system in the general eduction Baghdad hospital using Q GERT - رضا, صباح منفي; عبد الامير, رقية ياسر (Journal of Economics and Administrative Sciences, 2013)
That the essential contribution of this research is a description of how complex systems analysis service of the properties of the queue in Baghdad Teaching Hospital using a technique network is techniques method (Q - GERT) an acronym of the words: Queuing theory _ Graphical Evaluation and Review TechniqueAny method of assessment and review chart where you will be see the movement flow of patients within the system and after using this portal will be represented system in the form of planned network probabilistic analysis and knowledge of statistical distributions appropriate for times of arrival and departure were using the program ready (Win QSB) and simulation data collected directly from (9) Section service-hospital time two-hour no (120) minutes during peak time of time (12 - 10) at noon, for the purpose of data analysis and knowledge of statistical distributions appropriate has been used statistical program ready (STATGRAPHICS PLUS 4.0) was tested data in the same program testing (Good ness of fit), and after analyzing the data it was concluded that the best distribution of arrival times was normal distribution (Normal distribution) and the best distribution for times departure was distributed gamma (Gamma distribution) and all sections except sections of registration and pharmacy using normal distribution of times of arrival and departure , where system will be built on a queuing network of nodes and branches, through which we will get to hold a wait and we process these nodes develop solutions that lead to the solution of the constraints resulting impact of suffocation caused by waiting .